Analysis of the Influence of Service Quality on Customer Satisfaction and Loyalty in the Digital Service Industry: Insight from Online Shoppers in Indonesia - Barkah Setiawan; Yolanda Masnita; Kurniawati Kurniawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study focuses on digital service users in Indonesia, and aims to explore the influence of customer satisfaction and service quality on customer loyalty in digital service organizations. A random sampling technique was used to obtain a sample of 105 people consuming digital services in Indonesia. Partial Least Squares (PLS) analysis, a subset of Structural Equation Modeling (SEM), was used to evaluate the collected data. The findings of this study indicate a positive and statistically significant correlation between customer satisfaction and customer loyalty, supported by a Beta coefficient of 0.270, a T statistic of 2.946, and a p-value of 0.003. A Beta coefficient of 0.525, a T statistic of 6.186, and a p-value of 0.000 indicate that service quality has a significant and statistically significant influence on customer satisfaction. Furthermore, empirical studies show that the influence of service quality is statistically significant. Based on a Beta value of 0.411, a T statistic of 4.350, and a p-value of 0.000, it can be observed that the influence of service quality on customer loyalty is significant and strong. Thus, it can be concluded that in the digital services industry in Indonesia, the most important variables in determining customer loyalty are customer satisfaction and service quality.